Thermo-Hygral Case-Study on Full Scale RC Building under Corrosive Environment and Seismic Actions - Chijiwa, Nobuhiro; Maekawa, Koichi (Journal of Advanced Concrete Technology, 2015)
This paper is to apply the multi-scale thermo-hygro-mechanistic modeling to full-scale RC structural systems under combined long-term ambient and short seismic actions. The authors also aim to dissolve numerical difficulty for full-scale performance assessment of huge degree-of-freedom. First, the multi-scale modeling is experimentally checked by using corroded RC columns under high axial compression. Second, the steel corrosion is computationally reproduced to a multi-story RC building under long-term fictitious ambient conditions. The seismic ground motion is subsequently applied to the corrosion damaged mockup. Beforehand, the effect of drying shrinkage, which is inevitable for structural concrete in air, is discussed so as to clarify the pure corrosion impact to the whole structural system. The steel corrosion deteriorates the ductility of seismic resistant members, but as a global influence, steel corrosion is validated to reduce the base-shear input of floors owing to the decayed stiffness by corrosion. Through these case-studies, the authors raise the points of discussion to take into account the local and global effects of corrosion all at once for seismic performance assessment, and that the knowledge solely on the capacity of corroded RC members cannot lead to an engineering solution.